Visual Outcomes after Secondary Intraocular Lens Implant in Aphakic Children - Hussain, Shuja; Bukhari, Sadia; Raza, Ali; Abdul Rehman (Indus Journal of Bioscience Research, 2025)
Background: Aphakia in children, particularly following early cataract surgery, poses significant challenges for visual rehabilitation. Objective: This study aimed to evaluate the visual outcomes and postoperative complications following secondary IOL implantation in pediatric aphakic patients. Methods: This prospective observational study was conducted at Al Ibrahim Eye Hospital from May 2023 to May 2024. and included 102 aphakic children aged 1–12 years who underwent secondary IOL implantation. Patients were followed for a minimum of three months postoperatively. Best-corrected visual acuity (BCVA) before and after surgery was assessed, along with refractive outcomes and the incidence of complications. Results: The mean age at surgery was 5.2 ± 2.3 years. Sulcus placement was the most common fixation technique (40.2%), followed by scleral-fixated (33.3%) and iris-fixated IOLs (26.5%). BCVA significantly improved from 0.89 ± 0.27 logMAR preoperatively to 0.46 ± 0.22 logMAR postoperatively (p < 0.001). Visual acuity improved in 80.4% of children. Better outcomes were observed in bilateral aphakia (76.2% achieved BCVA ≤ 0.5 logMAR) compared to unilateral cases (53.8%) (p = 0.03). Postoperative complications occurred in 20.6% of patients, with posterior capsular opacification (8.8%) and glaucoma (4.9%) being the most common. Compliance with amblyopia therapy was significantly associated with better visual outcomes (p = 0.01). Conclusion: Secondary IOL implantation in aphakic children is a safe and effective intervention, leading to significant visual improvement. Outcomes are optimized when combined with consistent amblyopia therapy and regular follow-up.